Профессор Ц.Доржийн амьдрал бүтээлээс: Life and works by Professor Ts.Dorj - Х., Гаадан (Mongolian Studies, 2023)
The great teacher Ts. Dorj, who is filled with an energetic desire to learn and who has dedicated his life to supporting others with his teachings, remains alive and well among us at the age of 80. Dorj was bom at the end of 1885, in the family of the herder Tseveg. He herded livestock with his parents until the age of 20, at which point he followed his parents’ wishes and moved to Huree, where he began to learn Tibetan. Rather than simply memorizing Tibetan sutras as religious prayers, he attempted to appreciate the full meaning of these texts. This led to his being conferred the title of “gavj” (geshe) after several years in recognition of his scholarly achievement, identifying him as a master of the ten Buddhist sciences.